Cell Type-specific Induction of the Major Immediate Early Enhancer of Human Cytomegalovirus by Cyclic AMP - Thomas Stamminger; H. Fickenscher; B Fleckenstein (1990)
The major immediate early enhancer of human cytomegalovirus (HCMV) is known to exert a strong constitutive transcription stimulation in a broad spectrum of cells. This basal activity can be augmented considerably by elevated levels of intracellular cAMP in a cell type-specific manner. Cyclic AMP induction was observed in several lymphoid cell lines and in HeLa cells. One of the functionally important enhancer sequence modules, the 19 bp repeat element, mediates this effect as a cAMP-responsive element (CRE). It acts more efficiently than the corresponding sequence from the human chorionic gonadotropin gene. It is suggested that protein kinase C is involved in the pathway which leads to the activation of CRE- containing genes in lymphoid cells. Gel retardation assays indicated that similar, but not identical complexes are formed between nuclear protein extracts and the CREs of HCMV and the gonadotropin gene.